Use of Laser therapy in the emergency department for apical periodontitis post endodontic treatment - Diana Cristina Hernández del Haya; Claudia María Redondo Rodríguez; Yilianne Mirabal Pérez; María Cristina del Haya Rodríguez (Universidad Médica Pinareña, 2020)
Introduction: Laser therapy and stimulation of the acupuncture points are anti-inflammatory and analgesic alternative treatments in dentistry.